Multiple mini interviews (MMI): A perspective on the first year of MMI at Brighton and Sussex Medical School. (1st February 2018) - Tryb, Simonne
Abstract: Since it was developed at McMaster University School of Medicine in 2002, multiple medical interviews (MMI) have become a popular and accepted method of assessing candidates applying for medical training. Unlike a traditional panel interview it resembles the objective structured clinical examination (OSCE) with numerous 8–10 min stations assessing different topics or scenarios pertinent to medical training and healthcare. This was the first year of implementing MMI at Brighton and Sussex Medical School and my first year of interviewing. I found the process engaging and thought provoking.